Controlled Release of the Anticancer Drug Cyclophosphamide from a Superparamagnetic β-cyclodextrin Nanosponge by Local Hyperthermia Generated by an Alternating Magnetic Field - Diaz-Saldivar, P (American Chemical Society, 2023)
A β-cyclodextrin (β-CD) nanosponge (NS) was synthesized using diphenyl carbonate (DPC) as a cross-linker to encapsulate the antitumor drug cyclophosphamide (CYC), thus obtaining the NSs-CYC system. The formulation was then associated with magnetite nanoparticles (MNPs) to develop the MNPs-NSs-CYC ternary system. The formulations mentioned above were characterized to confirm the deposition of the MNPs onto the organic matrix and that the superparamagnetic nature of the MNPs was preserved upon association. The association of the MNPs with the NSs-drug complex was confirmed through field emission scanning electron microscopy, energy dispersive spectroscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, dynamic light scattering, ζ-potential, atomic absorption spectroscopy, X-ray powder diffraction, selected area electron diffraction, and vibrating-sample magnetometer. The superparamagnetic properties of the ternary system allowed the release of CYC by utilizing magnetic hyperthermia upon the exposure of an alternating magnetic field (AMF). The drug release experiments were carried out at different frequencies and intensities of the magnetic field, complying with the “Atkinson-Brezovich criterion”. The assays in AMF showed the feasibility of release by controlling hyperthermia of the drug, finding that the most efficient conditions were F = 280 kHz, H = 15 mT, and a concentration of MNPs of 5 mg/mL. CYC release was temperature-dependent, facilitated by local heat generation through magnetic hyperthermia. This phenomenon was confirmed by DFT calculations. Furthermore, the ternary systems outperformed the formulations without MNPs regarding the amount of released drug. The MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) assays demonstrated that including CYC within the magnetic NS cavities reduced the effects on mitochondrial activity compared to those observed with the free drug. Finally, the magnetic hyperthermia assays showed that the tertiary system allows the generation of apoptosis in HeLa cells, demonstrating that the MNPs embedded maintain their properties to generate hyperthermia. These results suggest that using NSs associated with MNPs could be a potential tool for a controlled drug delivery in tumor therapy since the materials are efficient and potentially nontoxic. © 2024 American Chemical Society.